Architectural approaches to housing customization: Introducing the Inhabitant-Driven Customization approach and the MyChanges tool - Eloy, S.; Vermaas, P. (Archnet-IJAR International Journal of Architectural Research, 2022)
Purpose Customization is a paradox in architecture, providing necessary modernization for buildings but potentially damaging their architectural integrity. In this paper, the authors introduce the Inhabitant-Driven Customization approach for avoiding this paradox; this approach lets inhabitants design the customization from options created by architects that safeguard architectural rules. As a first implementation of the Inhabitant-Driven Customization approach, the MyChanges tool is presented. The authors assess whether the approach avoids the customization paradox by a qualitative stakeholder evaluation of the MyChanges tool and by a comparison of the Inhabitant-Driven Customization approach with existing approaches to housing customization. Design/methodology/approach MyChanges is a shape grammar-based design tool developed to enable inhabitants of the Álvaro Siza Vieira Malagueira housing complex to customize their houses in accordance with the architectural language of the complex. In this study, the authors qualitatively evaluated MyChanges with architects and other professional stakeholders. MyChanges is used in this paper to assess if the Inhabitant-Driven Customization approach avoids the paradox of customization. The initial reception of MyChanges produced diverging outcomes, suggesting that Inhabitant-Driven Customization is also unable to avoid the customization paradox. For analyzing this possibility further, this paper describes the main existing approaches to housing customization, including the Inhabitant-Driven Customization approach, formulates nine conditions for these approaches, and provides a qualitative comparative assessment of the approaches. Findings The customization paradox is demonstrated in the outcomes of the interviews with professional stakeholders on the MyChanges customization tool for the Malagueira housing complex. An argument is given that makes plausible that the Inhabitant-Driven Customization approach avoids the customization paradox by creating a co-design process in which inhabitants and architects alternately shape customization. Originality/value The originality of this paper lies in the introduction and discussion of the paradox of customization in housing. The paper identifies the conditions advanced in architecture for assessing housing customization approaches. Additionally, the authors propose a new customization approach and a design tool that to a large extent fulfills those conditions and avoids the customization paradox.